Comparison of Pregnancy Outcomes between Lupus Nephritis Patients and Nonlupus Nephritis Systemic Lupus Erythematosus Patients at a Tertiary Care Center in Mumbai - Preeti Mehta Nagnur; Sandeep Yadav; C. Balakrishnan; Jatin Kothari; Rohini Samant; Gurmeet Mangat (Indian Journal of Kidney Diseases)
Background: Systemic lupus erythematosus (SLE) is a challenging autoimmune disease, particularly for women of reproductive age, and its impact on pregnancy is further complicated by lupus nephritis (LN). Objective: The aim is to study differences in pregnancy outcomes of patients with and without LN. Materials and Methods: A retrospective analysis of pregnant SLE patients who visited a rheumatology OPD and a combined LN clinic between 2004 and 2013 was performed. Results: The analysis included 91 pregnancies in 56 patients, 39 pregnancies in 21 patients with LN, and 52 in 35 patients without LN. The mean age at conception was 24 ± 3.80 years, with lower rates of successful pregnancy outcomes in patients with LN (35.9% vs. 63.5%) and higher spontaneous abortion rates (64.1% vs. 32.9%). A significantly increased occurrence of gestational hypertension (23% vs. 9.6%) and preeclampsia (7.6% vs. 0%) was observed in the LN group. Lupus flares were more prevalent in the LN group than in the non-LN group (61.5% vs. 28%). Fetal outcomes showed higher fetal loss in patients with LN (64.1% vs. 32.9%). Preterm births were similar, and full-term vaginal deliveries were higher in patients with SLE without LN (28.8% vs. 5%). The risk factors for poor outcomes in patients with LN included active renal disease and low C3 levels. Conclusion: LN patients face a more significant burden of adverse maternal and fetal outcomes, highlighted by higher rates of gestational hypertension, eclampsia, and fetal loss. These findings emphasize the necessity for an extended period of disease remission before planning pregnancy and tailored care for patients with LN.